High carbon load in food processing industrial wastewater is a driver for metabolic competition in aerobic granular sludge - Paulo, Ana M. S. (2021)
Aerobic granular sludge (AGS) processes are among the most robust wastewater treatments. One of their greatest advantages is related to the granules multi-layered structure, which creates a protective barrier against organic shock loads and variable wastewater composition, particularly attractive for the treatment of industrial wastewater. However, when treating a wastewater with variable and complex composition, the difficulty in identifying factors that most affect a specific biological process increases. In this study, the effect of organic loading rate (OLR), namely carbon content, on nitrification in an AGS process treating fish canning wastewater was investigated. Besides process performance, also biomass structural changes, and microbial community composition were analysed. Reactor operation lasted for 107 days and was divided in three phases during which different OLR and C/N ratios were applied. A higher OLR was applied during the first two phases (ca. 1.1 and 1.5 kg COD m−3 day−1, respectively) compared to the third phase (between 0.12 and 0.78 kg COD m−3 day−1) and the C/N ratios also varied (ca. 4.4, 7.8, and 2.9, respectively). Throughout the operation, COD concentration in the outlet was lower than 100 mg O2 L−1. Nitrification was inhibited during the second phase and recovered afterwards. Principal component analysis (PCA) of quantitative image analysis (QIA) and performance data allowed to distinguish process changes over the three operational phases. During the first two phases, the decrease in the biomass robustness occurred, but recovered during the last phase, indicating that the high content of organic matter had possibly an effect on the aerobic granules structural characteristics. The composition of the AGS microbiome did not change substantially after the end of the higher OLR periods. The main microbial diversity shifts were mostly associated to adaptation to higher or lower carbon availability. Bacteria and inferred enzymes associated to nitrogen and phosphorous removal were identified. Chryseobacterium, a bacterium with high metabolic versatility, was able to adapt to the organic shock load, becoming dominant over operation. Despite the variable composition of the fish canning wastewater, carbon was identified as the main driver for nitrification inhibition, while promoting changes in the physical characteristics and on the microbial community of granules.